Characterization in mice of the resident mesenchymal niche maintaining AT2 stem cell proliferation in homeostasis and disease. (15th June 2021) - Taghizadeh, Sara; Heiner, Monika; Vazquez‐Armendariz, Ana Ivonne; Wilhelm, Jochen; Herold, Susanne; Chen, Chengshui; Zhang, Jin San; Bellusci, Saverio
Abstract: Resident mesenchymal cells (rMCs defined as Cd31 Neg Cd45 Neg Epcam Neg ) control the proliferation and differentiation of alveolar epithelial type 2 (AT2) stem cells in vitro. The identity of these rMCs is still elusive. Among them, Axin2 Pos mesenchymal alveolar niche cells (MANCs), which are expressing Fgf7, have been previously described. We propose that an additional population of rMCs, expressing Fgf10 (called rMC‐Sca1 Pos Fgf10 Pos ) are equally important to maintain AT2 stem cell proliferation. The alveolosphere model, based on the AT2‐rMC co‐culture in growth factor‐reduced Matrigel, was used to test the efficiency of different rMC subpopulations isolated by FACS from adult murine lung to sustain the proliferation and differentiation of AT2 stem cells. We demonstrate that rMC‐Sca1 Pos Fgf10 Pos cells are efficient to promote the proliferation and differentiation of AT2 stem cells. Co‐staining of adult lung for Fgf10 mRNA and Sftpc protein respectively, indicate that 28% of Fgf10 Pos cells are located close to AT2 cells. Co‐ISH for Fgf7 and Fgf10 indicate that these two populations do not significantly overlap. Gene arrays comparing rMC‐Sca1 Pos Axin2 Pos and rMC‐Sca1 Pos Fgf10 Pos support that these two cell subsets express differential markers. In addition, rMC function is decreased in obese ob/ob mutant compared to WT mice with a much stronger loss of function in males compared to females. In conclusion, rMC‐Sca1 Pos Fgf10 Pos cells play important role in supporting AT2 stem cells proliferation and differentiation. This result sheds a new light on the subpopulations of rMCs contributing to the AT2 stem cell niche in homeostasis and in the context of pre‐existing metabolic diseases. Abstract : The mesenchyme is still a black box. It contains many subpopulations which remain to be characterized. In particular, the Cd31 Neg Cd45 Neg Epcam Neg cells (called resident mesenchymal cells or rMC) positive for Sca1 (rMC‐Sca1 Pos ) have been reported to support epithelial stem cell self‐renewal. We have used a robust and reproducible flow cytometry strategy associated with the alveolosphere assay to characterize further this subpopulation. Our results indicate that rMC‐Sca1 Pos Fgf10 Pos ‐LIFs as well as rMC‐Sca1 Pos LT Pos ‐LIFs support AT2 stem cell proliferation and differentiation. We have also compared this subpopulation to the previously described rMC‐Sca1 Pos Axin2 Pos cells. Our results indicate that they are likely two distinct populations. In addition, we demonstrate that rMC‐Sca1 Pos function is impaired in ob/ob male mice compared to ob/ob female mice and wild type mice regardless of their gender. This observation may be relevant in the context of COVID‐19 where obesity associated with the male gender represent important risk factors leading to poor prognosis.